The inhibition of hepatitis B virus by APOBEC cytidine deaminases. Issue 12 (December 2013) - Janahi, E. M.; McGarvey, M. J.
Summary: APOBEC3 (A3) cytidine deaminases are a family of enzymes that have been shown to inhibit the replication of HIV‐1 and other retroviruses as part of the innate immune responses to virus infection. They can also hyperedit HBV DNA and inhibit HBV replication. Although A3 proteins are present at low levels in normal liver, A3 gene expression is highly stimulated by both interferon‐α and interferon‐γ. A3 deaminases are incorporated into nascent HBV capsids where they cleave amino groups from cytidine bases converting them to uracil in newly synthesized DNA following reverse transcription of pregenomic RNA. This modified HBV DNA is susceptible to degradation, or alternatively, numerous G‐to‐A nucleotide mutations are incorporated into positive‐strand viral DNA disrupting coding sequences. A3 proteins in which the cytidine deaminase activity has been lost can also inhibit HBV replication, suggesting that there may be more than one way in which inhibition can occur. There is also evidence that A3 proteins might play a role in the development of hepatocellular carcinoma during chronic HBV infection.